La motivación como fuente de productividad en un call center - Vargas Caldas, Paola Andrea (Universidad Antonio Nariño, 2022)
Currently, BPO & Contact Center companies face the challenge of meeting the efficiencygoals established with their corporate clients, leading them to adopt process improvementmethodologies and techniques that allow them to meet these indicators and improve their productivity levels. The present work is carried out with the objective of determining those motivational factors that can influence the productivity of the collaborators in a call center, for this an investigation was carried out with qualitative methodology using the survey as a study instrument; This was done to 7 people who work or have worked in this type of industry, there were 5 open questions where they could express their opinion regarding the experience obtained, after having analyzed each of their answers, it was obtained as a result that the factor that generates a better motivation is the economic one, which inspires the collaborators to carry out their functions in an efficient way, generating a better experience for the users and greater profits for the company, the motivation in a call center is a very important pillar so that everything worker can give their maximum performance and thus generate greater productivity and profits.